Pengaruh Profitability Terhadap Penerapan Konservatisme Akuntansi Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index - Mulyani Rizki; M. Najib (Pusat Riset dan Inovasi Nasional, 2023)
To find out the company's financial condition in one period, it is reviewed through the financial statements issued by the company. The information for interested parties such as creditors, investors, government and users of financial statements is the responsibility of company management. Components in the presentation of its financial statements that already exist in PSAK No. 1 with issuance from the Indonesian Accounting Association, these components include the company's statement of financial position, the income statement, the report on changes in the company's equity, the report on its cash flows and the notes to the financial statements. 1 As for one of the methods in compiling a financial report issued by companies, namely the preparation of financial reports using the principle of accounting conservatism. Accounting conservatism includes actions taken to present the company's financial statements using the precautionary principle in which the company slows down recognizing profits and assets and accelerates recognizing losses and debts. The consequence of using this principle can result in lower profit and income values while costs tend to be relatively high. 2 The benefits of using conservatism can minimize risks to managers who have excessive optimism. However, excessive use of the principle of conservatism can cause differences in profits and losses by not reflecting the actual state of the company3 Judging from the above phenomenon, profitability can be a consideration in the application of accounting conservatism in companies listed on the Jakarta Islamic Index The purpose of this research is to find out how profitability affects the application of accounting conservatism in companies listed on the Jakarta Islamic Index. The number of samples in the research in this study amounted to 42 samples using a quantitative approach. The technique used in taking the sample uses non-probability sampling techniques, namely techniques in taking samples from the population where members of the population do not have the same opportunity to be used as samples. In this non-probability sampling technique, the researcher uses a purposive sampling technique, namely the sampling technique is based on certain criteria or requirements set by the researcher. The data obtained is processed using Eviews and the research data is panel data. The results of this study indicate that the value of tcount = 2.741973 > table = 1.68957 with probability = 0.0096 <α = 0.05. Based on this comparison it can be stated that Profitability has a significant positive influence on the application of accounting conservatism so that if the Profitability variable increases, the accounting conservatism variable will also increase